Association of C- Reactive Protein and HbA1c in the Severity of Coronary Artery Disease in Patients with Ischemic Heart Disease (Cardiovascular Journal, 2018)
Background: C-reactive protein (CRP) and glycohemoglobin (HbA1c) are established risk factors for the development of cardiovascular disease. We investigated the joint effects of these parameters on the severity of coronary artery disease (CAD) in patients with ischemic heart disease.Methods: This cross sectional study was performed on 668 patients of ischemic heart disease. CRP value were divided into normal (10 mg/L) and HbA1c was divided